Using Hypermedia in Teaching Art & Design: Baroque Dutch Paintings - Alkholy, Inas A. (International Journal of Emerging Technologies in Learning (iJET), 2010)
Although the whole world adapts ICT -information and communication technologies- in learning and teaching visual arts for the benefit of both the student and the society, the Middle East is motionless. ME teachers need training, institutional support and motivation to apply ICT in classrooms. Preparing a traditional lecture, including visual projected examples by data show takes less time. Doing comparisons and contrast, going through formal analysis or juggling between visual examples is complex within classrooms' technological limitations of having one projector. There is an urgent need to alter traditional methods of teaching art and design and integrate pictorial approaches. This paper discusses design/art pedagogy via a suggested model lesson, which utilizes hypermedia to resemble internet interface. The lesson teaches Dutch Baroque interior design through a selection of Vermeer's paintings. Vermeer accurately painted interior elements in his paintings. The development of technology stimulates studentsâ?? imagination and develops their understanding of more influencing graphical forms. Any other art and design themes and styles can be taught by using the same interface.